2005
DOI: 10.1186/1471-2350-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Common variants of the beta and gamma subunits of the epithelial sodium channel and their relation to plasma renin and aldosterone levels in essential hypertension

Abstract: Background: Rare mutations of the epithelial sodium channel (ENaC) result in the monogenic hypertension form of Liddle's syndrome. We decided to screen for common variants in the ENaC βand γ subunits in patients with essential hypertension and to relate their occurrence to the activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 38 publications
0
40
1
Order By: Relevance
“…The recruitment and characteristics of referred hypertensive patients have been described previously. 15 In brief, patients referred to the Hypertension Outpatient Ward of Helsinki University Central Hospital because of hypertension resistant to drug treatment were studied. Secondary hypertension was excluded with appropriate clinical and laboratory examinations.…”
Section: Methods Subjectsmentioning
confidence: 99%
“…The recruitment and characteristics of referred hypertensive patients have been described previously. 15 In brief, patients referred to the Hypertension Outpatient Ward of Helsinki University Central Hospital because of hypertension resistant to drug treatment were studied. Secondary hypertension was excluded with appropriate clinical and laboratory examinations.…”
Section: Methods Subjectsmentioning
confidence: 99%
“…Patients with the variant alleles showed an increased urinary potassium excretion rate in relation to their renin levels. 41 No increase in channel activity could be detected when these ENaC variants were expressed in Xenopus oocytes. Thus, the functional relevance of these variants remains uncertain.…”
Section: ␤Enacmentioning
confidence: 99%
“…41 At least 9% of Finnish patients with hypertension, admitted to a specialized center, carry genetic variants of ␤ENaC and ␥ENaC, a 3ϫ higher prevalence than in the normotensive individuals or in random healthy controls. Patients with the variant alleles showed an increased urinary potassium excretion rate in relation to their renin levels.…”
Section: ␤Enacmentioning
confidence: 99%
“…Gene variants of ENaC (epithelium sodium channel) (Hannila-Handelberg et al, 2005) and of CYP3A5 enzyme (11-hydroxysteroid dehydrogenase type 2) (Givens et al, 2003;Ho et al, 2005) have been demonstrated, focusing attention on sodium homeostasis, and on cortisol and corticosterone metabolism but the clinical relevance of these mutations is unclear.…”
Section: Prevalencementioning
confidence: 99%